Meta-Analysis: Depression as A Risk Factor for Dementia - Hesthi Krisnawati (Masters Program in Public Health, 2022)
Background: Depression is a mental disorder which if not treated can cause other diseases, including the individual's physical condition. One of the risks that occur due to recurrent depression is dementia. Dementia can reduce a person's ability to survive due to decreased brain function. This study was aimed to determine the effect of depression (depression) as a risk factor for dementia (dementia).Subjects and Method: This study was a meta-analysis, with a PICO covering Population= people with dementia. Intervention= depression. Comparison= without depression. Outcome= the risk of dementia. Research data was searched from several sources including: PubMed, Google Scholar, Springer Link, and Science Direct from 2011 until 2021 with the following keywords